The Effect of Capital Structure, Growth, and Firm Size on Firm Value: Case Study on Infrastructure Industry Companies Stated on the IDX 2019 - 2023 - Ardelia, Sarah Selli; Gurendrawati, Etty; Armeliza, Diah (LPPM Universitas Negeri Jakarta, 2024)
This research aims to determine the impact of capital structure, growth, and firm size affect the infrastructure industry companies stated on the Indonesia Stock Exchange (IDX) from 2019 and 2023 in terms of their firm value. The sample size was determined using purposive sampling. The research employed secondary data, which was sourced from the 2019 until 2023 financial statements of infrastructure companies. The multiple linear regression analysis method was applied in this investigation. Version 26 of SPSS was used to an analyze the data. The findings of this research indicated that a firm's value is influenced by its capital structure, growth, and size.